An exploration into the impact of care staff attitudes towards men who have sexually offended - Challinor, L.E. (2019)
Background: Understanding attitudes towards men who have sexually offended has been a research interest for many years. The existing research provides inconsistent findings, making it difficult to draw firm conclusions regarding the factors that are related to the attitudes that people hold towards men who sexually offend. This is an important area to understand, both for society, and for institutions that detain men who have sexually offended. Attitudes towards men who have sexually offended is related to the way in which the men engage in therapeutic treatment and also the way in which they can be successfully re-integrated into society. The thesis is motivated by a need to better understand the factors that are associated with the attitudes that people hold towards men who sexually offend and what changes are required to clinical practice to make positive improvements. Though each chapter is presented in sequence, they can be regarded as four independent studies, each of which utilise a different methodological design but are thematically linked.